Complete mitochondrial genomes and phylogenetic analysis of native and non-native fishes in a national key wetland of China - Zhang, Rui-Qing; Bai, Yang-Wei; Hu, Jian-Tao; Wang, Peng-Yuan; Qi, Yan; Zhang, Tian-Xu; Jiao, He-Yang; Lin, Xiao-Long; Yan, Zhen-Guang (Frontiers in Environmental Science, 2024)
Fish are considered objective indicators of environmental health and ecosystem stability. Establishing regional reference databases of mitochondrial genome sequences from local fish communities can significantly enhance fish monitoring using environmental DNA (eDNA) analysis. For non-native species, the eDNA technique provides early detection and rapid monitoring. It is also crucial to include fundamental genetic information for both native and non-native species in genetic databases. This study presents the complete mitochondrial genomes of 17 fish species inhabiting the Baiyangdian Basin, a national key wetland in China. The mitochondrial DNA of these fish was analyzed to investigate their characteristics, and their phylogeny was determined using maximum likelihood (ML) methods. Various analyses were performed, including the examination of nucleotide composition, evaluation of AT-skew and GC-skew, analysis of codon frequency, and determination of relative synonymous codon usage (RSCU) values, and assessment of selection pressure on protein-coding genes (PCGs). The analysis showed that all PCGs in all fish underwent purifying selection. Using Xenocyprididae as a representative, this study investigated the genetic selection tendencies of native and non-native fish species in the Baiyangdian Basin. Significant differences were found in five of the 13 PCGs: COI, COII, COIII, Cytb, and ATP8. Except for ATP8, the findings indicated that the genes of non-native species underwent stronger purifying selection during evolution compared to native species. Additionally, comparing the population 𝜔 values of non-native species to those of native species showed that the Cytb and COIII genes exhibited greater differential purification selection than COI and COII. These differences may be the result of the evolution of non-native species to migrate and adapt to the Baiyangdian Basin, thereby affecting the evolution of related genes.